2002
DOI: 10.1063/1.1482142
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature observation of high-spin polarization of epitaxial CrO2(100) island films at the Fermi energy

Abstract: Epitaxial CrO 2 (100) island films have been grown on TiO 2 (100) substrates by a chemical-vapor deposition technique. Well-controlled surface and interface properties of the CrO 2 (100) films were confirmed by scanning tunneling microscopy and transmission electron microscopy, respectively. Spin-and angle-resolved photoemission spectroscopy at room temperature revealed an energy gap of about 2 eV below Fermi level E F for spin-down electrons and a spin polarization of about ϩ95% at E F . After extended sputte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
93
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 21 publications
4
93
2
Order By: Relevance
“…[14] Third, the present system has unique symmetry that ensures its topological character and is composed of two highly industrialized oxides, for which process technologies are rather mature for fabrication of the heterostructure. [20,21] In summary, we demonstrated that the interfacial electrons at the CrO 2 /TiO 2 heterojunction can be fashioned into single-spin Dirac states. In the superlattice model, we can obtain a Chern number = 2 QAH phase, which will enable dissipationless digital signal transmisstion with minimal influence of noise.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…[14] Third, the present system has unique symmetry that ensures its topological character and is composed of two highly industrialized oxides, for which process technologies are rather mature for fabrication of the heterostructure. [20,21] In summary, we demonstrated that the interfacial electrons at the CrO 2 /TiO 2 heterojunction can be fashioned into single-spin Dirac states. In the superlattice model, we can obtain a Chern number = 2 QAH phase, which will enable dissipationless digital signal transmisstion with minimal influence of noise.…”
mentioning
confidence: 76%
“…Bulk CrO 2 (structure shown in Fig. 1) is a robust half metal even at elevated temperatures, [19][20][21] and widely used in enterprisegrade data storage. Here, we consider the possibility to fashion the CrO 2 into single-spin Dirac states by interfacial orbital design.…”
mentioning
confidence: 99%
“…There have been various arguments in favor of [27][28][29][30][31][32][33] and against 3,9,10,15-17 true half-metallic ferromagnetism. In our opinion, half-metallic ferromagnetism is an idealized limit, realistic only in perfect crystals at zero temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a somewhat ambiguous scanning tunneling microscopy spectroscopy study undertaken at 77 K, 79 claims of 100% spin polarization at more elevated temperatures ͑Ͼ40 K͒ rest on evidence from spin-polarized photoemission [75][76][77] and spinpolarized inverse photoemission, 78 as summarized in Table I. Spin-resolved photoemission measurements [75][76][77] and spinpolarized inverse photoemission 78 that claim to provide evidence of half-metal behavior, in fact, do not. ͑Of course, not all such measurements of potential half-metallic systems have led to such claims.…”
Section: Experimental Proof Of Half-metallic Ferromagnetismmentioning
confidence: 99%